IMPLEMENTATION OF CYBER PUBLIC RELATION MEDIA CHARACTER IN BUILDING THE ORIGINOTE BRAND IMAGE ON TIKTOK SOCIAL MEDIA IN 2021 - NESYA RIVKA; YUNITA SARI; HADIATI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
This research focuses on issues within The Originote TikTok account, including algorithm malfunction, lack of involvement from the public relations team in using TikTok, and the inaccuracy of digital implementation from the public relations team to the production team. With the aim of exploring cyber public relations implementation on TikTok and understanding the information delivery methods by The Originote's public relations team, this research employs cyber public relations media character theory and qualitative methods. The research results show a significant increase, with The Originote TikTok account reaching a high level of popularity. These findings are expected to provide practical guidelines for strengthening brand image on TikTok and improving digital implementation practices.